Resolving a 150-year-old paternity case in Mormon history using DTC autosomal DNA testing of distant relatives. (September 2019) - Perego, Ugo A.; Bodner, Martin; Raveane, Alessandro; Woodward, Scott R.; Montinaro, Francesco; Parson, Walther; Achilli, Alessandro
Highlights: We propose the resolution of a 150-year old alleged paternity using autosomal DNA data collected from 56 living descendants. This study deals with the posterity of Joseph Smith Jr., founder of Mormonism, and with the practice of plural marriage. This is a rare case of a possible polyandric relationship, where one woman is married to more than one man at the same time. We have determined portions of the genetic profile of Joseph Smith by genotyping the autosomal genome of his living posterity. We have also sequenced the entire mitochondrial DNA from a descendant of Katherine Smith, one of Joseph Smith Jr's sisters. Abstract: Although autosomal DNA testing has been available for a number of years, its use to reconstruct genetic profiles of people that lived centuries in the past is relatively recent and there are no published cases where it was employed to verify a kinship relation, likely to be an alleged paternity, that occurred one and a half century ago. DNA testing has already been employed to study the ancestry and posterity of Joseph Smith Jr., founder of the Latter-day Saint (Mormon) movement. Thanks to information found on the paternally inherited Y chromosome, a number of alleged paternities have been disproved, but obviously this analysis is not effective for alleged daughters. Likewise, his reconstructed mitogenome sequence, reported here for the first time, provides information about his maternal ancestry, but is useless in any paternity questions due to the strict maternal inheritance. Among all the children attributed to Joseph Smith Jr., Josephine Lyon, born in 1844, is perhaps the most frequently mentioned. In the current study, 56 individuals, mostly direct descendants of Joseph Smith Jr. and Josephine Lyon, had their autosomal DNA tested to verify Josephine's biological paternity. Nearly 600, 000 autosomal SNPs from each subject were typed and detailed genealogical data were compiled. The absence of shared DNA between Josephine's grandson and Joseph Smith Jr.'s five great-grandchildren together with various amounts of autosomal DNA shared by the same individual with four other relatives of Windsor Lyon is a clear indication that Josephine was not related to the Smith, but to the Lyon's family. These inferences were also verified using kinship analyses and likelihood ratio calculations.